2009
DOI: 10.1136/vr.164.26.803
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anaesthesia with either midazolam or propofol in rabbits premedicated with fentanyl/fluanisone

Abstract: Fifty-four rabbits that were to be neutered were premedicated with 0.1 ml/kg fentanyl/fluanisone and then randomly allocated to be anaesthetised with either midazolam or propofol. Anaesthesia was then maintained with isoflurane. The ease of orotracheal intubation, the rabbits' cardiorespiratory variables, and the speed and quality of recovery from anaesthesia were assessed by the same anaesthetist who was unaware of the induction agent used. Hypotension was common in both groups. The mean (sd) respiratory rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Blood pH decreased from 7.50 ± 0.00 to 7.28 ± 0.04 and serum lactate from 1.9 ± 0.6 to 0.7 ± 0.2 mmol/L (n = 7). The arterial partial pressure of O 2 (PaO 2 ) increased from 9.6 (8.4-11.1) to 38 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) kPa whereas mean arterial pressure (MAP) decreased during anaesthesia ( Table 2). Heart rate (HR) and cardiac output (CO, n = 6) increased immediately after induction and remained high during most of maintenance ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood pH decreased from 7.50 ± 0.00 to 7.28 ± 0.04 and serum lactate from 1.9 ± 0.6 to 0.7 ± 0.2 mmol/L (n = 7). The arterial partial pressure of O 2 (PaO 2 ) increased from 9.6 (8.4-11.1) to 38 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) kPa whereas mean arterial pressure (MAP) decreased during anaesthesia ( Table 2). Heart rate (HR) and cardiac output (CO, n = 6) increased immediately after induction and remained high during most of maintenance ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The heart rate increased after induction with TIVA, although the values did not reach the levels reported in awake unrestrained rabbits [37]. A possible explanation for the increase is the sympathomimetic stimulation caused by endotracheal intubation [38]. Alpha-2-agonists are able to block cardiovascular responses caused by intubation and surgery in humans [39] and opioids can block the sympathetic response to surgery in dogs [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Alfaxalone shares similar properties with propofol (Taboada and Murison 2010, Gil and others 2012). Propofol, although known to be safe in small mammal anaesthesia, is known to induce apnoea in rabbits and requires strict intravenous use (Martinez and others 2009). Some data have shown that alfaxalone is effective when administered intramuscularly in cats and rabbits, bypassing the need for intravenous injection and the associated stress of handling (Marsh and others 2009, Grubb and others 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[3032] In an animal model, rabbits premedicated with fentanyl followed by induction of anesthesia with midazolam resulted in hypotension with reduced quality of recovery. [33] Similar reports of hypotension with the combined use of fentanyl and midazolam have been documented during electrophysiological procedures,[34] and sedation and anesthesia. [3536] Moreover, in preterm babies (<33 weeks gestational age), midazolam is associated with adverse neurological events.…”
Section: Discussionmentioning
confidence: 69%